2016
DOI: 10.1177/0394632016659301
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of rush allergen-specific immunotherapy in Chinese allergic rhinitis patients

Abstract: The purpose of this prospective, open-IV clinical trial was to assess the safety and efficacy differences between Rush immunotherapy (RIT) and conventional immunotherapy in Chinese allergic rhinitis (AR) patients. The trial involved 174 patients with AR. They were divided into two groups according to their preference of therapy: RIT or conventional immunotherapy. A total of 162 patients completed a 1-year treatment course. For safety and effectiveness evaluation, the local and systemic adverse reactions were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…In this study, we observed that LTA4 and LTB4 were increased, followed by arachidonic acid, which is in accordance with this theory [22]. LTB4, synthesized by LTA4 hydrolase from LTA4, is a leukotriene involved in inflammation that plays an important role in the development of AR [23]. These results indicated that arachidonic acid metabolism was also disordered in our study, and with high VIP, arachidonic acid might be used as a specific candidate biomarker for AR.…”
Section: Metabolomics Studysupporting
confidence: 88%
“…In this study, we observed that LTA4 and LTB4 were increased, followed by arachidonic acid, which is in accordance with this theory [22]. LTB4, synthesized by LTA4 hydrolase from LTA4, is a leukotriene involved in inflammation that plays an important role in the development of AR [23]. These results indicated that arachidonic acid metabolism was also disordered in our study, and with high VIP, arachidonic acid might be used as a specific candidate biomarker for AR.…”
Section: Metabolomics Studysupporting
confidence: 88%
“…RIT shows similar and even earlier onset of clinical efficacy compared to conventional AIT, and there is no evidence to support a difference in systemic adverse reactions [157]. Similarly, the cluster schedule reduced the time to reach maintenance dose and caused mild systemic adverse reactions with no differences compared to conventional schedules [158,159].…”
Section: Rush and Cluster Immunotherapy Schedulesmentioning
confidence: 98%
“…However, there is no standard RIT protocol around the world. Generally, 1 injection every 1-3 hours or even 1 injection every 15-60 minutes over a period of maintenance phase from about 4 hours to 7 days has been employed (29,(203)(204)(205). RIT is currently used mostly for bee venom and grass pollen immunotherapy.…”
Section: Ritmentioning
confidence: 99%
“…RIT is currently used mostly for bee venom and grass pollen immunotherapy. Apart from SLIT, dust mites subcutaneous RIT has been reported less frequently (29,(206)(207)(208). Also, there is some evidence that the shortened treatment time of RIT, results in improved patient compliance to high allergen doses on resuming a conventional AIT schedule (209).…”
Section: Ritmentioning
confidence: 99%
See 1 more Smart Citation